-5c+7-6c=-59

Simple and best practice solution for -5c+7-6c=-59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5c+7-6c=-59 equation:


Simplifying
-5c + 7 + -6c = -59

Reorder the terms:
7 + -5c + -6c = -59

Combine like terms: -5c + -6c = -11c
7 + -11c = -59

Solving
7 + -11c = -59

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -11c = -59 + -7

Combine like terms: 7 + -7 = 0
0 + -11c = -59 + -7
-11c = -59 + -7

Combine like terms: -59 + -7 = -66
-11c = -66

Divide each side by '-11'.
c = 6

Simplifying
c = 6

See similar equations:

| 40k^2-3k-0.3=0 | | y=.5+.7x | | -5/6/-4 | | 12000=0.8v-0.08v*6 | | 1/3p+3=15 | | 6/11x | | 1/4r+9=10-3/3r | | 9600=0.8*20000-0.08*20000y | | 9-2(-8+4)=17 | | 10b+40(0.90b)+30(0.80b)=525 | | 45-[4-2y-4(y+7)]=-4(1+3y)-[4-3(y+2)-2(2y+5)] | | 3=3x-2y | | 9-2(8+4)=17 | | 2(5c+3)-25=6c+1 | | 8/5x+3/x | | 1/4/80 | | 7.65=2.25+20(m-1) | | -3=k/7-3 | | 9-2(x+4)=17 | | (k-4h)(4h+k)=0 | | 4y=x+1 | | 6.05=2.25+20(m-1) | | 7x-3=8x+1 | | (12*x)/13=6 | | 3w+5w=32 | | -14=-9+a/3 | | -2/3x+30=-92 | | 12*x/13 | | 45n=270 | | 12x/13 | | g(x)=x^2+8x+1 | | 9n+1=37 |

Equations solver categories